Portrait of Islamic Learning in the Muallaf Village - Sayamsuddin Nur; Iin Chandradewi (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
This research departs from the phenomenon of transformation of religious beliefs (conversion) which occurred in a village which is now called the village of converts precisely in Lapela village, Siwalalat District, Eastern Seram Regency. This research uses a qualitative approach. Results of this research shows that the Muslim community in the village converted to Islam from the start converting to Islam feels no difficulty in learning the teachings of the Islamic religion, However, this does not mean that it is free from all kinds of challenges and even problem. In studying Islam there are several aspects that arise Barriers include: economic aspects, teaching staff resources as well facilities and infrastructure